ON INTERNAL QUALITY AND SAFETY CONTROL OF MEDICAL ACTIVITY IN NEWBORNS WITH INTESTINAL ATRESIA - M. A. Shishov; Т. A. Polynskaya (Медицинский вестник Юга России, 2016)
Objectve: establishment of evaluation criteria used in the framework of internal quality control in newborns with intestinal atresia. Materials and methods: for the realization of the goal studied regulations governing the relevant aspects of health care. Results: the study was formed lists criteria for evaluation. Conclusions: the use of these criteria aimed at optimizing organizational models activity pediatric surgery, allowing you to eventually may become one of the components of actions aimed at reducing infant mortality in Rostov Region.